2019
DOI: 10.1002/mnfr.201900636
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Clostridium butyricum against Microglia‐Mediated Neuroinflammation in Alzheimer's Disease via Regulating Gut Microbiota and Metabolites Butyrate

Abstract: Scope: Recent evidences demonstrate that abnormal gut microbiota (GM) might be involved in the pathogenesis of Alzheimer's disease (AD). However, the role of probiotics in preventing AD by regulating GM-gut-brain axis remains unclear. Here, the anti-neuroinflammatory effect and its mechanism of probiotic Clostridium butyricum (CB) against AD is investigated by regulating GM-gut-brain axis. Methods and results: APPswe/PS1dE9 (APP/PS1) transgenic are treated intragastrically with CB for 4 weeks then cognitively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
162
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(169 citation statements)
references
References 47 publications
4
162
3
Order By: Relevance
“…Furthermore, butyrate-producing microbiota were diminished in elder patients with Alzheimer's disease (Haran et al, 2019). Recently, the butyrate-producing probiotic, Clostridium butyricum, was found to have an anti-neuroinflammatory effect in Alzheimer's disease (Sun et al, 2020). This effect was mediated via butyrate by regulating the gut-brain axis (Sun et al, 2020).…”
Section: Promising Areas Of Research In Bacterial Infection Volatilomementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, butyrate-producing microbiota were diminished in elder patients with Alzheimer's disease (Haran et al, 2019). Recently, the butyrate-producing probiotic, Clostridium butyricum, was found to have an anti-neuroinflammatory effect in Alzheimer's disease (Sun et al, 2020). This effect was mediated via butyrate by regulating the gut-brain axis (Sun et al, 2020).…”
Section: Promising Areas Of Research In Bacterial Infection Volatilomementioning
confidence: 99%
“…Recently, the butyrate-producing probiotic, Clostridium butyricum, was found to have an anti-neuroinflammatory effect in Alzheimer's disease (Sun et al, 2020). This effect was mediated via butyrate by regulating the gut-brain axis (Sun et al, 2020). Therefore, butyrate and other volatile short-chain fatty acids are promising preventive and therapeutic interventions in Alzheimer's disease.…”
Section: Promising Areas Of Research In Bacterial Infection Volatilomementioning
confidence: 99%
“…Type 2 diabetes mellitus (T2DM) is the fourth most common non-transmissible disease. Frequent weight loss, high urination, thirst, and poor foot lesions healing power are the most common symptoms, which may later lead to complications, such as coronary heart diseases, obesity, retinopathy, sexual weakness, kidney failures, and atherosclerosis ( Sun J. et al, 2020 ). T2DM has multifactor roots, including physiological, psychological, genetic, and environmental factors ( Ardeshirlarijani et al, 2019 ).…”
Section: Health-boosting Spectrum Of Probioticsmentioning
confidence: 99%
“…Additionally, several studies have reported that there is a relationship between AD and specific gut microbiota, such as Helicobacter pylori , Porphyromonas gingivalis, and Actinomycetes (Dominy, Lynch, & Ermini, 2019; Emery et al., 2017; Franceschi, Ojetti, & Candelli, 2019). Some studies have shown that probiotics, such as Lactobacillus, Bifidobacterium, and Clostridium, reduce amyloid β (Aβ) deposition, neurofibrillary tangles, and neuroinflammation, and improve cognitive dysfunction (Lee, Lee, Kim, & Kim, 2019; Nimgampalle & Kuna, 2017; Sun, Xu, & Yang, 2020). In one study, a germ‐free (GF) mouse model of AD showed a reduction in cerebral Aβ amyloid pathology, yet did not evaluate cognitive function (Harach et al., 2017).…”
Section: Introductionmentioning
confidence: 99%